Sprawdź i popraw błedy
a)(2x+y)(x-2y)-x(x+y)=2xkwadrat-4xy+xy-2ykwadrat-xkwadrat+xy=xkwadrat-2xy-2ykwadrat
b) (3a-2b)(a-b)+2(a-b)(a-2b)=3akwadrat-3ab-2ab+2bkwadrat+2(akwadrat-2ab-ab+2bkwadrat)=5akwadrat-10ab+6bkwadrat
c) (4k+1)(2k-1)-(k-1)(k-3)=8k kwadrat-4k+2k-1-(k kwadrat+3K-k+3)=7k kwadrat-4k-4

1

Odpowiedzi

  • Użytkownik Zadane
2009-10-27T08:59:05+01:00
A)(2x+y)(x-2y)-x(x+y)=2x² -4xy+xy-2y² -x² -xy =2x²-x²-4xy+xy-xy-2y²=
x²-4xy-2y²
b) (3a-2b)(a-b)+2(a-b)(a-2b)=3a² -3ab-2ab+2b² +2(a² -2ab-ab+2b²)=3a²+2a²-3ab-2ab-4ab-2ab+2b²+4b²=5a²-11ab+6b²
c) (4k+1)(2k-1)-(k-1)(k-3)=8k²-4k+2k-1k²+3k-1-k+3=7k²+2